Inhibitors of collagenase but not of gelatinase reduce cartilage explant proteoglycan breakdown despite only low levels of matrix metalloproteinase activity. Issue 6 (December 1996) - Brown, Carol J; Rahman, Shamim; Morton, Allison C; Beauchamp, Claire L; Bramwell, Helena; Buttle, David J
Abstract : Aims —To investigate the level of matrix metalloproteinase activity during the time-course of cartilage explant proteoglycan breakdown; to determine the effects of selective small-molecule inhibitors of matrix metalloproteinases on proteoglycan degradation. Methods —The levels of matrix metalloproteinase activity in cartilage explant cultures and conditioned media were monitored by use of a quenched fluorescent substrate. The constants for inhibition of certain matrix metalloproteinases by a series of synthetic inhibitors were determined. Bovine and human cartilage explant cultures were treated with interleukin-1, tumor necrosis factor or retinoic acid and the amount of proteoglycan released into the culture medium in the absence and presence of the inhibitors was quantified. Control experiments, examining the inhibition of other proteinases, and investigating possible toxic or non-specific effects of the inhibitors, were carried out. Results —The profile of inhibition of proteoglycan release suggested the involvement of interstitial collagenase-like, rather than gelatinase- or possibly stromelysin-like, proteinases. No evidence was found for toxic or non-specific mechanisms of inhibition. Very low levels of activity of the known matrix metalloproteinases were present during the time-course of aggrecan breakdown. Conclusions —A novel collagenase-like proteinase(s) may be involved in cartilage proteoglycan breakdown. Gelatinase-type matrix metalloproteinases do not seem to be involved in this process. Specific collagenase inhibitors may be therapeutically efficacious in the treatment of arthritis.